A new hierarchical belief-rule-based method for reliability evaluation of wireless sensor network. (August 2018) - He, Wei; Hu, Guan-Yu; Zhou, Zhi-Jie; Qiao, Pei-Li; Han, Xiao-Xia; Qu, Yuan-Yuan; Wei, Hang; Shi, Chun
Abstract: With the wide applications of wireless sensor network (WSN), its reliability evaluation has been attracted more attention. The reliability of a WSN is affected mainly by internal and external factors, which include internal faults and external attacks. In this paper, a reliability evaluation method based on a hierarchical belief rule base (BRB) method is proposed for the reliability evaluation of the WSN. First, the factors affecting the reliability of a WSN are analysed, and the reliability evaluation process that considers the WSN fault evaluation and WSN security evaluation is described. Second, the reliability evaluation model is constructed based on the hierarchical BRB model. The qualitative knowledge is used by the BRB model to build initial belief rules, and the quantitative data are used to optimize the initial parameters of the BRB model, which can utilize various types of uncertainty information effectively. Therefore, the proposed method can be applied to the WSN reliability evaluation, which is a complex and uncertain problem. Finally, a simulation case study and an actual case study of wellhead blowout monitoring are conducted to verify the effectiveness of the proposed method. The reliability results of actual WSN are obtained by the standard testing method, where the loss and accuracy rates of the collected data are treated as the observation factors for obtaining the actual reliability values. The estimated results of hierarchical BRB model are very close to the actual reliability values, which shows that the proposed method can be used for evaluating the reliability of the actual WSN accurately. Highlights: To solve the problem of WSN reliability evaluation, a new hierarchical Belief-Rule-Based (BRB) method is proposed. The WSN reliability evaluation model is constructed based on the evaluation of WSN faults and WSN security. The model can effectively use the semi-quantitative information to establish a nonlinear model. The simulation and real case are implemented. The method can be effectively applied to WSN reliability evaluation.